Talking to Gen Z About Media and Pseudoscience: Trends and Perceptions - Anna Podara; Theodora Saridou; Ioanna Kostarella; Elissavet Georgiadou; Andreas Veglis (Societies)
This paper explores Gen Z’s understanding of science and pseudoscience, assessing, at the same time, their media literacy skills. Drawing on the relevant literature and elaborating on the findings from five focus groups studies in remote areas of Greece and Portugal, it sheds light on how young people perceive science. Through a synthesis of the insights garnered from the participants’ personal experiences, this study endeavors to offer valuable advice and recommendations for designing education material that is tailor-made to address the needs of generation Z. By adopting these suggestions, policymakers and educational experts can advance scientific literacy, cultivate critical thinking, and nurture an environment of evidence-based decision-making for young people.